Safeguarding the Enforcement of Human Rights Obligations Towards Indigenous Peoples in Cameroon (African Journal of Law and Politics, 2025)
The responsibility to protect and enforce the rights of indigenous peoples lie principally with States as they are the bearers of human rights obligations that stem from both customary and treaty law. Despite the fact that the choice of domestic enforcement mechanisms are the sovereign right of States, international law imposes certain minimum requirements with respect to indigenous peoples. This paper reviews what chances are there for the realisation of the human rights obligations towards indigenous peoples in Cameroon. To arrive at the desired results, the paper adopted a socio-legal analytical research method, examining existing measures which are available to the State for the effective enforcement of the human rights obligations towards indigenous people. Findings suggest that despite the constitutional marginalisation that indigenous people suffer in Cameroon, they can readily enjoy direct and indirect enforcement of their rights. Indirect enforcement refers to indigenous rights that are not well-defined and are therefore incapable of direct/immediate enforcement. The State has to undertake some positive acts, such as a legislative or administrative or policy measure, exercising a high level of political discretion when it comes to the enforcement of indigenous rights and may do as it pleases or confidently lie on its pillow of lethargy.